Validation of a stability-indicating RP-LC method for the determination of tigecycline in lyophilized powder - Da Silva, Lucélia Magalhães [UNESP]; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2013)
A reversed-phase liquid chromatography (RP-LC) method was validated for the determination of tigecycline in lyophilized powder. The LC method was conducted on a Luna C18 column (250 × 4.6 mm i.d.), maintained at room temperature. The mobile phase consisted of buffer containing sodium phosphate monobasic (0.015M) and oxalic acid (0.015M) (pH 7.0)-acetonitrile (75:25, v/v), run at a flow rate of 1.0 mL/min and using ultraviolet detection at 280 nm. The chromatographic separation was obtained with a retention time of 8.6 min, and was linear in the range of 40-100 μg/mL (r2 = 0.9997). The specificity and stability-indicating capability of the method was proven through forced degradation studies, which also showed no interference of the excipients. The accuracy was 99.01% with a bias lower than 1.81%. The limits of detection and quantitation were 1.67 and 5.05 μg/mL, respectively. Moreover, method validation demonstrated satisfactory results for precision and robustness. The proposed method was applied for the analysis of the lyophilized powder formulation, contributing to improve the quality control and to assure the therapeutic efficacy. © The Author [2012]. Published by Oxford University Press. All rights reserved.
Keywords: drug derivative; minocycline; tigecycline; chemistry; drug stability; limit of detection; methodology; powder; reproducibility; reversed phase liquid chromatography; standard; statistical model; Chromatography, Reverse-Phase; Drug Stability; Limit of Detection; Linear Models; Minocycline; Powders; Reproducibility of Results